Exploring the Prevalence of Ayurveda Use Among Asian Indians - Yumi E. Satow, Praveena D. Kumar,Adam Burke, and John F. Inciardi (THE JOURNAL OF ALTERNATIVE AND COMPLEMENTARY MEDICINE Volume 14, Number 10, 2008, pp. 1249-1253, 2008)
Objective: Despite a growing body of literature on complementary and alternative medicine, there is still limited information on the use of Ayurveda in the United States. Because Ayurveda is one of the world's major traditional medical systems, knowledge of its use is important. In particular, information on utilization by Asian Indians living in the United States is needed due to increased immigration from India and related regions. Recent reports of heavy metal contamination of some imported Ayurveda products underscore this need. For this reason, an exploratory survey was conducted. Design: A semistructured 21-item questionnaire was administered using face-to-face interviews.Participants and setting: The study comprised a convenience sample of 64 Asian Indians living in Northern California. Outcome measures: Main outcome measures included sociodemographic variables, questions on awareness, knowledge and use of Ayurvedic products or services, use of other nutritional/herbal products, and reasonsfor use. Results: In the sample, 95 per cent of the participants were aware of Ayurveda, 78 per cent had knowledge of Ayurvedic products or treatments, and about 59 per cent had used or were currently using Ayurveda. Only 18 per cent of those using Ayurveda had informed their Western medical doctors. Conclusions: Given its common use in the United States by Asian Indians, its cultural relevance, potential therapeutic value, and possible safety concerns, physician and consumer education along with more empirical research is warranted.